Pengaruh Variasi Gliseril Monostearat pada Krim Ekstrak Kulit Buah Naga Merah Super (Hylocereus costaricensis) dan Uji Antioksidannya - Nugrahaeni, Fitri; Yati, Kori; Sukmara, Sukmara (Jurnal Kefarmasian Indonesia, 2023)
A Glyceryl monostearate can be used as an emulsifier because it can affect the increase in antioxidant activity. The study aims to determine the effect of fluctuations in the concentration of glyceryl monostearate (GMS) on the physical properties of cream preparations containing 70% ethanol extract from the skin of super red dragon fruit and their antioxidant activity. The research methods carried out experimentally include the manufacture of extracts from super red dragon fruit peel, phytochemical screening using thin layer chromatography, formulations using various concentrations of glyceryl monostearate 8%, 10%, 12% then the physical quality of the cream and antioxidant activity test using the DPPH method. The results of one-way ANOVA for pH, dispersion, adhesion, and viscosity tests showed a p-value of> 0.05, indicating that there was no significant difference. The IC50 results obtained with equations 1, 2, and 3 are 3.69 mg/L, respectively. 3.98mg/L; and 4.78mg/L. Formula 3 is the best formula and estimates the antioxidant activity of Vitamin C, which is a positive control, at a value of 5.83 mg/L. The results of the irritation test showed that none of the formulations caused irritation. The preference test results showed that the respondents liked all the formulas. The conclusion of this study is that increased fluctuations in the concentration of glyceryl monostearate did not affect the physical properties of super red dragon fruit skin extract cream, but did affect its antioxidant activity.